Ответ:
Объяснение:
2х² - 5х + 2 = 0
D = b² - 4ac = (-5)² - 4 * 2 * 2 = 25 - 16 = 9
D>0 будет два корня
х₁ =
x₂ =
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
2х² - 5х + 2 = 0
D = b² - 4ac = (-5)² - 4 * 2 * 2 = 25 - 16 = 9
D>0 будет два корня
х₁ =![\frac{-b+\sqrt{D} }{2a}=\frac{-(-5)+\sqrt{9} }{2*2}=\frac{5+3}{4}=\frac{8}{4}=2 \frac{-b+\sqrt{D} }{2a}=\frac{-(-5)+\sqrt{9} }{2*2}=\frac{5+3}{4}=\frac{8}{4}=2](https://tex.z-dn.net/?f=%5Cfrac%7B-b%2B%5Csqrt%7BD%7D%20%7D%7B2a%7D%3D%5Cfrac%7B-%28-5%29%2B%5Csqrt%7B9%7D%20%7D%7B2%2A2%7D%3D%5Cfrac%7B5%2B3%7D%7B4%7D%3D%5Cfrac%7B8%7D%7B4%7D%3D2)
x₂ =![\frac{-b-\sqrt{D} }{2a}=\frac{-(-5)-\sqrt{9} }{2*2}=\frac{5-3}{4}=\frac{2}{4}=\frac{1}{2}=0,5 \frac{-b-\sqrt{D} }{2a}=\frac{-(-5)-\sqrt{9} }{2*2}=\frac{5-3}{4}=\frac{2}{4}=\frac{1}{2}=0,5](https://tex.z-dn.net/?f=%5Cfrac%7B-b-%5Csqrt%7BD%7D%20%7D%7B2a%7D%3D%5Cfrac%7B-%28-5%29-%5Csqrt%7B9%7D%20%7D%7B2%2A2%7D%3D%5Cfrac%7B5-3%7D%7B4%7D%3D%5Cfrac%7B2%7D%7B4%7D%3D%5Cfrac%7B1%7D%7B2%7D%3D0%2C5)